IDENTIFIKASI PERKEBUNAN NANAS TERHADAP EKONOMI MASYARAKAT DESA AIR DUREN KABUPATEN BANGKA - Roidatul Baiti Baiti; Monanisa Monanisa; Wahyu Saputra (JURNAL GEOGRAFI, 2023)
The problem in this study is that the economic growth of the people of Air Duren Village, Bangka Regency, is influenced by the pineapple plantation sector because almost all of the population fulfills their daily needs from pineapple plantations. This study aims to determine and identify pineapple plantations to the economy of the people of Air Duren Village, Bangka Regency. The method used in research on the identification of pineapple plantations on the economy of the people of Air Duren Village, Bangka Regency, is a Qualitative Descriptive Method. Data collection techniques using observation techniques, interviews and documentation. The results of this study indicate that in a pineapple plantation on the economy of the people of Air Duren Village, Bangka Regency, almost all of the people of Air Duren Village have pineapple gardens. help to meet the daily needs of the community ranging from clothing, boards and food. In pineapple gardening, the capital spent from pineapple gardening is not too big, the maintenance is not too difficult, while the profits can increase income, and also with the existence of pineapple plantations, this has provided new opportunities for people and youth who do not have a job. So that it can provide benefits to the community around Air Duren Village because the existence of the pineapple plantation affects the economic condition of the local community.